INTER-LIMBS EFFECT, DIFFUSION AND STRENGTH PREDICTORS IN ARM FLEXORS (Journal of Biomedical Investigation, 2025)
Background: Strength training is a methodical exercise regimen that enhances muscle action, and is the act of repeated voluntary muscle contractions against a resistance greater than usually accomplished during activities of daily living. However, there are controversial reports on the effects of cross education and strength diffusion in untrained muscles.Aims: The aim of this study was to establish the inter-limb phenomenon between trained and untrained contralateral homologous muscle and other adjacent muscle groups of the trained extremity.Materials and Methods: Forty undergraduate students participated in this study. They were randomly assigned to 2 groups. For progression, One-Repetition Maximum (1-RM) was determined four times within six weeks isometric training of the arm flexors for participants in the experimental group (group 1) while participants in group 2 served as control. Using standard procedures, spring balance was used to measure the strength of the arm flexors and other selected muscles in both limbs, at onset and at the 6 th week. The Body Mass Index (BMI) was computed while height, weight, and girth were measured. Descriptive statistics, Paired and Independent t-tests; and ANOVA were used to analyze the data. Level of significance was set at 0.05.Results: There were significant differences between the right and left right arm flexor strength following 6 weeks isometric strength training in both the experimental and control groups (t = 6.57, p = 0.001; t = 5.10, p = 0.001). There were significant differences between the initial and final for both right and left right arm flexor muscle strength following 6 weeks isometric strength training (t = -7.95, p = 0.001; t = -8.97, p = 0.001 respectively) but none in the control group. There was only significant increase in the selected adjacent muscles in the experimental group despite that they were not trained (p = 0.001). Height was the most significant predictor of arm flexors strength, contributing 29% (p =0.005).Conclusion: There was cross education effect at the untrained contralateral homologous muscle (arm flexors) following 6 weeks training of the other opposite extremity. Similarly, there were strength gains in the untrained shoulder flexor, extensor, abductor, adductor; and extensor, muscle groups, implying strength diffusion. Also, height of the participants was the most significant predictor of arm flexors strength.
Keywords: Muscle Strength; Inter-limb effects; Diffusion; Isometric training; Arm flexors